MYCN-targeting vaccines and immunotherapeutics. Issue 9 (1st September 2016) - Schramm, Alexander; Lode, Holger
ABSTRACT: Amplification and concomitant overexpression of the MYCN oncogene is a frequent event in many malignancies including the childhood tumors, neuroblastoma and medulloblastoma. MYCN is only expressed in a defined time frame during early developmental processes, 1 which is beneficial for approaches combatting tumor-specific MYCN. However, MYCN is a transcription factors that was considered a poor drug target, until recent approaches suggested that down-regulation of MYCN could be possible by indirect targeting using Aurora kinase inhibitors or BET inhibitors. These concepts were proven using preclinical models 2–6 and are now entering clinical trials.